2018
DOI: 10.1007/s00059-018-4708-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction following coronary artery bypass grafting

Abstract: CABG is associated with prolonged ED, which is determined by the patient's preoperative inflammatory state rather than by CPB modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The off-pump method of surgical procedures described in our analysis allowed us to minimalize the influence of post-operative inflammatory response on our results. Several studies confirmed that the off-pump surgical revascularization technique omits the risk for inflammatory activation secondary to CBP administration [ 40 43 ]. In the Mirhafez et al [ 41 ] study serum cytokines levels in off-pump coronary surgery were lower compared with on-pump method.…”
Section: Discussionmentioning
confidence: 99%
“…The off-pump method of surgical procedures described in our analysis allowed us to minimalize the influence of post-operative inflammatory response on our results. Several studies confirmed that the off-pump surgical revascularization technique omits the risk for inflammatory activation secondary to CBP administration [ 40 43 ]. In the Mirhafez et al [ 41 ] study serum cytokines levels in off-pump coronary surgery were lower compared with on-pump method.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery induces a sepsis-like syndrome associated with a high degree of endothelial cell dysfunction. Recent studies report drastically increased postoperative levels of endothelial markers in blood such as vascular endothelial cadherin and endocan, which correlate with the severity of endothelial cell injury after cardiac surgery (33,34). Von-Willebrand factor regulates adhesion of immune cells to injured endothelium and has been previously studied in cardiac patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…When we look at the literature, the presence of ischemic areas after CABG surgery, the effects of long-term anesthesia, and high heart rate because of compensation by increasing heart rate instead of increasing stroke volume to increase cardiac output, are expected situations. This may indicate that myocardial oxygen consumption is still high (30).…”
Section: Exercise Training That Improves Diastolic Function Can Incre...mentioning
confidence: 99%